Otimização da eficiência dos ligantes em pastas através do empacotamento de partículas em microescala com substituição parcial de cimento Portland - Kebhard, Jonathan Mello (Universidade do Vale do Rio dos Sinos, 2023)
Civil construction consumes a lot of resources ad emits greenhouse gases, and Sustainability becomes one of the main focuses of attention. Among the materials used in the production of cementicious materials, Portland cement has the greatest environmental impact. In this context, the presente work proposes the application of a particle packing method to obtain pastes with greater binder efficiency, using mineral additions such as: sílica fume, limestone filler, granitic filler and pozzolanic ash, these additions being a positive point for Sustainability, which can reduce cement consumption, which has a great impact on CO2 emissions, on the scale of production. In the first stage, the fine materials were characterized. In step 2, the proportion of the fine materials was adjusted, seeking a lower IDE in relation to Alfred’s particle packing model. In the third step, two traits were proposed taking into account the ideal compositon of the paste in terms of stoichiometric calculations. In the fourth stage, the pastes were made, with spreading control in the fresh state. Observing in two types of curing, the pastes were charaterized in the hardened state, in terms of strength, with a photografic survey of the internal part of the test specimens to analyze the dispersion of the particles. In general, in the fresh state, pastes with better packing required more additives and had lower consistency. In the hardened state, the adjusted pastes did not reach the resistance potencial of the reference pastes, but obtained a better Binder efficiency index, with a reduction in the kg/MPa index of 42.5% in the pastes with cement CPII F-40 and 20.7% reduction in the pastes with cement CPIV 32. From na ideal paste contente adopted for concrete, it is calculated that there is the possibility of producing concrete with 3.0 kg/MPa. Evaluating in terms of Sustainability, based on the estimate adopted for concrete, the clinker factor was taken into account, making it passible to produce concrete with 2.4 kg of clinker for each MPa per m³ with cement CPII F-40 and 2.2 kg of clinker for CPIV 32 cement. The method used makes it possible to generate optimized pastes for concrete, with high performance and less environmental impact, due to the maximization of officiency in the use of binders.
Keywords: Empacotamento de partículas; Concreto; Microestrutura; Resistência e sustentabilidade; Particle packing; Concrete; Microstructure; Strength and sustainability; ACCNPQ::Engenharias::Engenharia Civil